PENERAPAN MODEL COURSE REVIEW HORAY TERHADAP KEMAMPUAN MENELAAH TEKS HIKAYAT OLEH SISWA KELAS X ASISTEN KEPERAWATAN SMK KARYA SETIA PEGAJAHAN TAHUN PEMBELAJARAN 2022-2023 - Putri, Rizka (Jurnal Bahastra, 2024)
The aim of this research is to find out: 1) The process of applying the ability to study history teks using the horay course review model for the first grade of nursing assistant students at SMK Karya Setia Pegajahan academic year 2022-2023. 2) Increase the quality of the learning process of studying history teks for students with the horay review course model for the first grade of nursing assistant students at SMK Karya Setia Pegajahan academic year 2022-2023. Data collection for this research was carried out by observation, written test, daily notes and documentation. The research results show : 1) Application of the horay review course model can improve student learning out comes in their ability to study history for the first grade of nursing assistant students at smk karya setia pegajahan. Students activity in cycle one in the learning process of studying history texts was 386 with a percentage of 80% and it was found that the results of observations showed that the learning outcomes of cycle one students in studying history teks showed an increase from pre-cycle after doing the questions were given, with an average score of 75 with a percentage of 66.6%. 2)Increasing the quality of the learning process studying history teks in cycle two, the total number of students was obtained 435 with a percentage of 91%. So this research is considered complete in improving student activity by applying the model “course revie horay”.